Revendiquer le "mariage gay" Belgique, France, Espagne - Paternotte, David (Science politique, 2011)
A new step in the process of legal recognition of same-sex unions, "gay marriage" is now being debated in many countries. This pioneering book examines the emergence of this demand in Belgium, Spain and France, three states where gay and lesbian activists demanded the right to marry early on.